The System of Proof is Reversed Against Corruption Offenses According to Islamic Law and Indonesian Law - Suaib, Hermanto; Hatta, Muhammad; Hamsir,; Bunyamin, (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is an extraordinary crime (extra ordinary crimes), so that extra-enforcement is needed. One of the efforts in the eradication of corruption in Indonesia is the application of a reverse proof burden system. In the aspect of Indonesian criminal law, the burden of reverse proof of corruption has been carried out and regulated in Article 12B, Article 12C, Article 37, 37A, Article 38A and 38B of Law No. 31 of 1999 Jo. Law No. 20 of 2001 concerning Eradication of Corruption Crimes. In the aspect of Islamic law, the application of the reverse proof burden system falls into the category of ta'zir based on government policy (ulil amri). The burden of reversing proof is implicit in the Qur'an, sura Yusuf, verses 26-29. However, in applying the inverse proof system, jurists use istihsan in making ijtihad on contemporary social problems.